2021
DOI: 10.3389/fmars.2021.666825
|View full text |Cite
|
Sign up to set email alerts
|

Differential Symbiodiniaceae Association With Coral and Coral-Eroding Sponge in a Bleaching Impacted Marginal Coral Reef Environment

Abstract: Marginal reefs are known for severe stress-inducible perturbations such as high sedimentation, eutrophication, ocean warming, and acidification from anthropogenic climate change. The corals striving in such stressful environments develop physiological adaptations induced by differential genomic expressions or association with thermal stress-tolerant algal symbionts (Symbiodiniaceae). Despite such adaptations, corals are threatened by other space competitors such as algae and sponges. Coral-eroding sponges belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…Surprisingly, background levels of algal symbionts from the genus Gerakladium were also identified in two samples. In general, this genus is not known to associate with scleractinian corals, but rather with excavating sponge species (Mote et al, 2021). It is possible that excavating sponge species were colonizing the M. cavernosa skeleton and perhaps small amounts may have been unintentionally collected in addition to the coral tissue.…”
Section: Cladocopium-dominated Symbiodiniaceae Communitiesmentioning
confidence: 99%
“…Surprisingly, background levels of algal symbionts from the genus Gerakladium were also identified in two samples. In general, this genus is not known to associate with scleractinian corals, but rather with excavating sponge species (Mote et al, 2021). It is possible that excavating sponge species were colonizing the M. cavernosa skeleton and perhaps small amounts may have been unintentionally collected in addition to the coral tissue.…”
Section: Cladocopium-dominated Symbiodiniaceae Communitiesmentioning
confidence: 99%
“…However, selectivity is not related to symbiont abundance in the environmental pool (Quigley et al, 2017 ). A study in the Central West Coast of India, which experienced multiple years of bleaching temperatures, found that despite the symbiont population in the surrounding water containing high abundances of both Durusdinium and Gerakladium , corals had higher relative abundances of Durusdinium (Mote et al, 2021 ). Despite symbiont assemblages in corals being dominated by Durusdinium , Gerakladium was also present in higher abundances (10.2 ± 11.7%) than typically found as a background symbiont (Mote et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study in the Central West Coast of India, which experienced multiple years of bleaching temperatures, found that despite the symbiont population in the surrounding water containing high abundances of both Durusdinium and Gerakladium , corals had higher relative abundances of Durusdinium (Mote et al, 2021 ). Despite symbiont assemblages in corals being dominated by Durusdinium , Gerakladium was also present in higher abundances (10.2 ± 11.7%) than typically found as a background symbiont (Mote et al, 2021 ). The growing number of observations of Gerakladium as a background coral symbiont in a variety of coral species could be a result of increased sampling and molecular methods, or due to an increase in the frequency Gerakladium is taken up by corals that might relate to environmental change or stress.…”
Section: Discussionmentioning
confidence: 99%
“…In many instances, some corals tolerate or recover better from bleaching than others in every geographical region including India (Kumaraguru, 2003; Manikandan et al, 2014; Pisapia and Burn, 2016; Thinesh et al, 2019a, De et al 2022, 2023). In India, studies are at a nascent state to identify the factors (symbiont types) responsible for differential bleaching patterns (for example Thinesh et al, 2019; Mote et al, 2021). Generally, massive taxa such as Porites spp.…”
Section: Introductionmentioning
confidence: 99%
“…Warmest months, thermal thresholds, and bleaching thresholds of Indian coral reefs regions by using NOAA OISST data from 1982 to 2018 based onArora et al 2019;and De et al 2021 …”
mentioning
confidence: 99%